2022
DOI: 10.1146/annurev-virology-100120-012345
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Viral RNA Degrading Factors in Shutoff of Host Gene Expression

Abstract: Many viruses induce shutoff of host gene expression (host shutoff) as a strategy to take over cellular machinery and evade host immunity. Without host shutoff activity, these viruses generally replicate poorly in vivo, attesting to the importance of this antiviral strategy. In this review, we discuss one particularly advantageous way for viruses to induce host shutoff: triggering widespread host messenger RNA (mRNA) decay. Viruses can trigger increased mRNA destruction either directly, by encoding RNA cleaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 182 publications
0
16
0
Order By: Relevance
“…Studies of viral host shutoff RNases have so far mostly relied on RNA steady-state levels as a proxy for RNA degradation. However, widespread RNA degradation can have multiple downstream effects on other aspects of RNA metabolism (Gaucherand and Gaglia, 2022). Thus, steady-state level analysis may preclude a clear understanding of how these enzymes target RNAs and which RNAs they directly degrade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of viral host shutoff RNases have so far mostly relied on RNA steady-state levels as a proxy for RNA degradation. However, widespread RNA degradation can have multiple downstream effects on other aspects of RNA metabolism (Gaucherand and Gaglia, 2022). Thus, steady-state level analysis may preclude a clear understanding of how these enzymes target RNAs and which RNAs they directly degrade.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that PA-X activity is not indiscriminate, as it down-regulates host RNAs synthesized by RNA Polymerase II (RNAPII) but not RNAPI and III 13 . Interestingly, this feature is shared by all characterized viral endoRNases and degradation factors that drive host shutoff 1,14 . In influenza A virus, this specificity may be explained by a connection between PA-X and cellular RNA splicing, which may govern how PA-X reaches its target RNAs 4 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…To harbour cellular environment and escape immunological response, viral factors interact with host transcription machinery to alter the expression of immune responsive genes including cytokines, interleukins etc. 8,9 RNA sequencing (RNA-seq) and ribosome profiling of Calu3 cells infected with SARS-CoV2 was performed to determine modulation in gene expression. It was observed that massive production of viral transcripts reduces the percentage of cellular transcripts.…”
Section: Sars-covand Transcriptional Machinerymentioning
confidence: 99%